ANALYSIS OF STUDENT LEARNING SATURATION IN ONLINE LEARNING SYSTEM (E_LEARNING) IN ENGLISH LESSONS AT SMPN 10 BARRU - Eka Adhy Saputra; St. Asriati; Ariana Ariana (FKIP Unismuh Makassar, 2022)
The research subjects were 8th grade students of SMPN in Barru. This study uses a qualitative method. This research design uses observation, interviews, and documentation, which consists of data reduction, display, and conclusion. This study revealed that the aspects of emotional exhaustion, physical exhaustion, mental fatigue and loss of learning motivation experienced by students when studying online caused some students to experience the impact of learning saturation during the COVID-19 pandemic and various factors that supported the occurrence of burnout, including consisting of: personal characteristics, social support and academic burden. Individuals who have low self-concept, are too perfectionist and idealistic, are unable to control their emotions and are less skilled in managing stress, experience learning saturation. The social support relates to the learning environment and the relationship between teachers, students and parents. While the academic burden in question is presenting too many or too few assignments, it certainly affect student learning outcomes, especially if the teacher also does not provide adequate explanations.